DAKWAH ISLAM: ANTARA HARMONISASI DAN DINAMISASI - Moh. Roqib (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
Harmony and dynamics in Da’wa activities should be continually developed in order to achieve Islam ’s mission as rahmatan lil’ alamin. Persistence, maturity, and sincerity should also be committed in creating fresh and peaceful Da’wa activities that people need. Harmony and dynamics in da ’wa activities should start from every individual and accustomed in the family to make it religious, academic, and morally respectful. Starting from the closest environment, such a da ’wa is expected to be widely spread out. People who have the need of da ’wa will be highly motivated to find it. Approaches, strategies, and cooperation with various elements need to be applied to reach such condition. In this case, harmony and dynamics should be the basic elements in achieving the goals of da ’wa activities.